Looking for the maximum low-temperature conductivity in selectively doped AlxGa1-xAs-GaAs-AlxGa1-xAs double heterojunctions - Simserides, C.D.; Triberis, G.P. (Journal of Physics Condensed Matter, 1996)
We use self-consistent numerical calculations to study the sheet electron concentration and the mobility as functions of the doping concentration, the spacer thickness, the well width and the Al mole fraction of a selectively doped AlxGa1−xAs/GaAs/AlxGa1−xAs double heterojunction, using no arbitrary, a priori, assumptions, at low temperatures.For the first time we take into account two kinds of donor (shallow and deep) that coexist in the Si-doped AlxGa1−xAs. We study all the significant scattering mechanisms. The model, based exclusively upon the knowledge of the material and structural parameters involved, allows us to obtain the maximum conductivity for any specific structure. Our results are in a very good agreement with experiment.